A novel bidirectional continuous perfusion bioreactor for the culture of large sized bone tissue engineered constructs - Gardel, Leandro S. (2013)
This works reports the development and preliminary assessment of a new bioreactor for culturing large sized 3D constructs in bone tissue engineering. The Bidirectional Continuous Perfusion Bioreactor (BCPB) promotes mechanical stimulation of cells through the creation of shear forces induced by flow perfusion. The main innovation consists in the possibility of culturing scaffolds of large dimensions that can be suitable for the regeneration of critical sized defects. The functionality of BCPB was preliminarily evaluated by culturing starch-polycaprolactone scaffolds/goat bone marrow stromal cells for 14 and 21 days. Cylindrical blocks were stacked (42 mm thick). Static culture was used as controls. The samples were collected for DNA, ALP, scanning electron microscopy and histological analysis. The results showed higher ALP levels in the bioreactor cultures than those obtained under static conditions. The number of cells in constructs cultured in the bioreactor showed lower values compared to static cultures, suggesting that static conditions tend to privilege the metabolic path way for cellular proliferation while dynamic conditions tend to privilege the metabolic path for osteogenic differentiation. SEM observations show that, the migration and  cell distribution was observed in the bioreactor. These results demonstrate the feasibility and the benefit of culturing constructs in BCPB.